The nursing profession: public image, self‐concept and professional identity. A discussion paper. (26th May 2013) - Hoeve, Yvonne ten; Jansen, Gerard; Roodbol, Petrie
Abstract Aim To discuss the actual public image of nurses and other factors that influence the development of nurses' self‐concept and professional identity. Background Nurses have become healthcare professionals in their own right who possess a great deal of knowledge. However, the public does not always value the skills and competences nurses have acquired through education and innovation. Design Discussion paper. Data sources We identified 1216 relevant studies by searching MEDLINE, CINAHL and PsycINFO databases in the period 1997–2010. Finally, 18 studies met our inclusion criteria. Discussion The included studies show that the actual public image of nursing is diverse and incongruous. This image is partly self‐created by nurses due to their invisibility and their lack of public discourse. Nurses derive their self‐concept and professional identity from their public image, work environment, work values, education and traditional social and cultural values. Implications for nursing Nurses should work harder to communicate their professionalism to the public. Social media like the Internet and YouTube can be used to show the public what they really do. Conclusion To improve their public image and to obtain a stronger position in healthcare organizations, nurses need to increase their visibility. This could be realized by ongoing education and a challenging work environment that encourages nurses to stand up for themselves. Furthermore, nurses should make better use of strategic positions, such as case manager, nurse educator or clinical nurse specialist and use their professionalism to show the public what their work really entails.